Hadith #2602 - Sunan Abi Dawud - al-Zubair bin al-Walid al-Shamy الزبير بن الوليد الشامي; Amr bin 'Uthman عمرو بن عثمان بن عفان; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; ibn Umar; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
Ali ibn Rabi’ah said: I was present with Ali while a beast was brought to him to ride. When he put his foot in the stirrup, he said: “In the name of Allah.” Then when he sat on its back, he said: “Praise be to Allah.” He then said: “Glory be to Him Who has made this subservient to us, for we had not the strength, and to our Lord do we return.” He then said: “Praise be to Allah (thrice); Allah is Most Great (thrice): glory be to Thee, I have wronged myself, so forgive me, for only
Grade: Sahih

Hadith #3795 - Sunan Abi Dawud - Abdur Rahman bin Shabal al-Ansari; Abu Rashid al-Hbrany أبو راشد الحبراني; al-Hakm bin Nafi', Abu al-Yaman الحكم بن نافع أبو اليمان الحمصي; Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
We were in an army with the Messenger of Allah (ﷺ). We got some lizards. I roasted one lizard and brought it to the Messenger of Allah (ﷺ) and placed it before him. He took a stick and counted its fingers. He then said: A group from the children of Isra’il was transformed into an animal of the land, and I do not know which animal it was. He did not eat it nor did he forbid (its eating).
Grade: Sahih

Hadith #4070 - Sunan Abi Dawud - Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Habib bin 'Ubaid al-Rhby حبيب بن عبيد الرحبي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
We went out with the Messenger of Allah (ﷺ) on a journey, and we had on our saddles and camels garments consisting of red warp of wool. The Messenger of Allah (ﷺ) said: Do I not see that red colour has dominated you. We then got up quickly on account of this saying of the Messenger of Allah (ﷺ) and some of our camels ran away. We then took the garments and withdrew them.
Grade: Da'if

Hadith #4348 - Sunan Abi Dawud - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Amr bin 'Uthman عمرو بن عثمان بن عفان; Sa'd ibn Abi Waqqas; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) led us in the night prayer one night towards the end of his life. When he uttered the salutation, he got up and said : Have you seen this night of yours ? No one of those who are on the surface of the earth will survive at the ends of one hundred years. Ibn ‘Umar said: The people fell into fallacy by this statement of the Messenger of Allah (ﷺ) about the traditions they used to narrate concerning one hundred years. The Messenger of Allah (ﷺ) said: No one of tho
Grade: Sahih

Hadith #4887 - Sunan Abi Dawud - Abu Umama bin Sahl; Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Jubayr bin Nufayr al-Hadrami; Kathir bin Marrah al-Hadrami كثير بن مرة الحضرمي; Sa'id bin 'Amr bin Sa'id bin al-Aas سعيد بن عمرو بن سعيد بن العاص; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
Is one of you unable to be like Abu Damdam? The people asked: who is Abu Damdam? He replied : A man of old before you. He then mentioned the rest of tradition to the tradition to the same effect. This version has : who would say (in the morning) : My honors is for the one who reviles me. Abu Dawud said: This tradition has also been transmitted by Hashim bin al-Qasim from Muhammad b. ‘Adb Allah al-‘Ammi from Thabit on the authority of Anas from Prophet (ﷺ) to the same effect. Abu Dawud said
Grade: Da'if

Hadith #5006 - Sunan Abi Dawud - Amr bin al-'Aas; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
The Prophet (ﷺ) said: On the Day of resurrection Allah will not accept repentance or ransom from him who learns excellence of speech to captivate thereby the hearts of men, or of people.
Grade: Da'if